Influence of season, age and postpartum interval on reproductive parameters of norgestomet treated anestrus zebu cattle - UMED SINGH,; SINGH, INDERJEET; KHAR, S K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on anestrus Zebu cattle randomly assigned either to receive Crestar treatment(n=82: 39 heifers+ 43 cows) or to remain untreated (n=24: 12 heifers+ 12 cows) for studying the effect of age,postpartum interval and season on their reproductive perfonnance. Reproductive perfonnance was not affectedby age of heifers (2.5 - 3.0 vs. 3 - 4 yr.) and postpartum interval (90-120 vs. 150 or more days). The encouragingresults of 71 - 100% estrus induction rate: 4 i- 72% first service conception rates and 65 - 83% overall conceptionrates suggested that heifers even at younger age could possibly be induced to estrus with this treatment. providedtheir physical condition are good: as well as the cows with even shorter postpartum interval. In addition, Crestareffectively induced fertile estrus in anestrus heifers and cows both during the hot as well as the cold months. Themean interval to estrus for heifers during hot season was significantly longer than the cold season suggesting thatheifers treated during hot months should be bred according to estrus for better fertility.
Keywords: Zebu cattle; norgestomet; anestrus; conception rate; age; season